Plainclothes [videorecording (DVD)] - Emmi, Carmen; Blyth, Tom, 1995-; Tovey, Russell; Dizzia, Maria, 1974-; Balazs, Alessandra Ford; Cooke, Christian, 1986-; Brownstein, Sam Asa (Magnolia Home Entertainment, 2026)
A promising undercover agent assigned to lure and arrest gay men defies professional orders when he falls in love with a target.